“Dear my dearest me”: Reading self-image through students’ haikus - Gandana, Isti Siti Saleha; Fadilah, Kemalylla Rose (Indonesian Journal of Applied Linguistics, 2026)
Adolescence is a critical stage in identity development, where individuals begin to define and express their self-image. This study explores how adolescent students construct their self-image through haiku, focusing on the diction, tone, and mood of their compositions. Drawing on Rosenberg’s (1989) theory of self-image, the study analyzed nine haikus written by second-year university students in Exploring Poetry class. Two central themes emerged: self-deprecation and self-appreciation. These themes reflect the degree to which the students’ present self-image aligns with their ideal self. The overall findings point to haiku’s potential as a creative medium that supports personal reflection and emotional awareness, serving as a meaningful outlet for identity exploration. By offering a non-intimidating medium for self-expression, haiku encourages students to engage with their internal states and articulate aspects of self that may otherwise remain unspoken. This research highlights the value of integrating reflective literary practices into the classroom as a pedagogical strategy to support adolescent development. In so doing, the study contributes to broader conversations on the role of creativity in fostering emotional and psychological well-being in educational contexts.